CN metabolism and nitrogen use efficiency of rice with different nitrogen form and rate. - Minji Kim; Boyun Lee; Jwakyung Sung (PLoS ONE)
Nitrogen (N) is one of crucial mineral nutrients for rice cultivation, however excessive N application has resulted in lower utilization and thus occasionally attributes to environmental impacts. Simultaneously, rice production requires greater watering, exacerbating water scarcity concerns. This study explores strategies to enhance nitrogen use efficiency (NUE) in rice, focusing on the carbon-nitrogen (CN) metabolism under different nitrogen conditions. Two rice cultivars (Oryza sativa L. cv. Samgwang-SG, and NIL Milyang#360-ML) were subjected to different nitrogen forms (ammonium sulfate-AS, ammonium nitrate-AN) and application rates (45 kg ha⁻¹ and 90 kg ha⁻¹). The results demonstrated that SG exhibited increased N assimilation in both leaves and roots under lower N input, while ML primarily superior on grain development. ML showed higher carbohydrate accumulation in leaves, potentially contributing to enhanced grain yield under low N conditions. Moreover, ammonium-sulfate (AS) proved more effective in promoting NUE than ammonium-nitrate (AN), particularly at lower N input (45N). Principal component analysis confirmed that 45N treatments positively correlated with improved nitrogen uptake and utilization efficiency, with no significant yield reduction. These findings highlight the importance of optimizing nitrogen management to improve NUE while reducing environmental impacts in rice production. A further study is required to evaluate and validate the nitrogen use efficiency under different N form and dose with a field scale.